RESEARCH OF THE STABILITY OF SCOPE BOARDS OF QUARRY BOARDS USING THE ENGINEERING METHOD - Sherali Raufovich , Urinov; Agzam Muratovich , Askarov; Sevara Abdukarim kizi , Mansurova; Kahramon Abdukhailovich , Akhmedov; Muzaffar Bakhtiyorovich , Mirzakhmedov (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
An engineering method for calculating the stability of slopes in quarries is considered, the slope angles of high ledges and the height of sub-ledges are established when forming a concave slope profile of a high ledge.